Mouse Gastric Epithelial Cells Resist CagA Delivery by the Helicobacter pylori Type IV Secretion System - Shrestha, Rejina; Murata-Kamiya, Naoko; Imai, Satoshi; Yamamoto, Masami; Tsukamoto, Tetsuya; Nomura, Sachiyo; Hatakeyama, Masanori (International journal of molecular sciences, 2022)
The initial step in bacterial infection is adherence of the bacterium to the target cell surface. Helicobacter pylori exploits the interaction of bacterial adhesin protein HopQ with human epithelial CEACAMs (CEACAM1, 5, and 6) to stably adhere to gastric epithelial cells, which is necessary for delivery of the H. pylori CagA oncoprotein into the epithelial cells via a type IV secretion system. In contrast to human CEACAMs, however, HopQ does not interact with Ceacam1 (mouse CEACAM1) in vitro or in CHO cells ectopically expressing Ceacam1. Since the mouse genome lacks Ceacam5 and Ceacam6, no significant HopQ–Ceacam interaction may occur in mouse gastric epithelial cells. Here, we found that the mouse stomach has a much lower expression level of Ceacam1 than the expression level of CEACAM1 in the human stomach. Consistently, mouse gastric epithelial cells resist CagA delivery by cagA-positive H. pylori, and the delivery is restored by ectopic expression of human CEACAM1 or CEACAM5 in mouse gastric epithelial cells. Thus, despite the fact that mice are routinely used for H. pylori infection studies, a low expression level of Ceacam1 in the mouse stomach together with the loss or greatly reduced interaction of HopQ with Ceacams make the mouse an inappropriate model for studying the role of H. pylori-delivered CagA in gastric pathogenesis, including the development of gastric cancer.